IMPLEMENTASI PERATURAN MENTERI SOSIAL NOMOR 1 TAHUN 2018 TENTANG PROGRAM KELUARGA HARAPAN (PKH) PERSPEKTIF MASLAHAH MURSALAH (Studi Kasus di Desa Sengkuang Jaya Kecamatan Seluma Barat Kabupaten Seluma) - Astria, Suci (UIN Fatmawati Sukarno Bengkulu, 2021)
Abstract: The formulation of this research is What are the substance of the implementation of the Minister of Social Affairs Regulation Number 1 of 2018 concerning the Family Hope Program, What are the supporting and inhibiting factors for the implementation of the Minister of Social Affairs Regulation Number 1 of 2018 concerning the Family Hope Program), How is the implementation of the Ministerial Regulation Social Affairs Number 1 of 2018 concerning the Family Hope Program from the Maslahah Mursalah Perspective. This type of research is field research (field research) with a qualitative approach. The results of the research substance from the implementation of the Minister of Social Affairs Regulation Number 1 of 2018 concerning the Family Hope Program are in accordance with the main content of this program reducing numbers and breaking the poverty chain, improving the quality of human resources, and changing welfare-enhancing behavior. The supporting and inhibiting factors for the implementation of the Minister of Social Affairs Regulation Number 1 of 2018 concerning are the assistance from the social service, the existence of complete data and adequate road access to reach the homes of residents and schools that receive, while the obstacle is the lack of human resources and sometimes there are some technical problems during disbursement. Implementation of the Minister of Social Affairs Regulation Number 1 of 2018 concerning the Family Hope Program Perspective of Maslahah Mursalah This family of hope program has become a benefit for the people of Sengkuang Jaya Village by using the maslahah mursalah theory in order to provide an illustration that a rule made will contain a benefit for the community which prioritizes the interests of maslahah al-ammah. Keywords: Minister of Social Affairs Regulation Number 1 2018, Family Hope Program, Maslahah Mursalah Perspective Abstrak: Rumusan penelitian ini adalah Apa saja substansi dari implementasi Peraturan Menteri Sosial Nomor 1 tahun 2018 tentang Program Keluarga Harapan (PKH), Apa saja Faktor pendukung dan penghambat pelaksanaan Peraturan Menteri Sosial Nomor 1 tahun 2018 tentang Program Keluarga Harapan (PKH), Bagaimana impelementasi Peraturan Menteri Sosial Nomor 1 tahun 2018 tentang Program Keluarga Harapan (PKH) Perspektif Maslahah Mursalah. Jenis penelitian ini adalah penelitian lapangan (field research) pendekatan kualitatif. Hasil penelitian substansi dari implementasi Peraturan Menteri Sosial Nomor 1 tahun 2018 tentang Program Keluarga Harapan (PKH) sudah sesuai dengan isi pokok dari program ini mengurangi angka dan memutus rantai kemiskinan, meningktkan kualitas sumber daya manusia, serta mengubah perilaku peningkatan kesejahteraan. Faktor pendukung dan penghambat pelaksanaan Peraturan Menteri Sosial Nomor 1 tahun 2018 tentang adalah adanya pendampingan dari dinas sosial, Adanya data yang lengkap dan akses djalan yang telah memadai untuk menjangkau rumah warga dan sekolah yang penerima PKH, sedangkan penghambatnya adanya kurangnya sumber daya manusia dan terkadang ada beberapa kendala secara teknis pada saat melakukan pencairan. Impelementasi Peraturan Menteri Sosial Nomor 1 tahun 2018 tentang Program Keluarga Harapan (PKH) Perspektif Maslahah Mursalah Program keluarga Harapan ini sudah menjadi sebuah kemaslahatan bagi masyarakat Desa Sengkuang Jaya dengan menggunakan teori maslahah mursalah agar dapat memberikan gambaran bahwa suatu aturan dibuat akan mengandung sebuah maslahat bagi masyarakat yang mana lebih mengutamakan kepentingan maslahah al-ammah. Kata Kunci : Peraturan Menteri Sosial Nomor 1 Tahun 2018, Program Keluarga Harapan (PKH), Perspektif Maslahah Mursalah